Analysis Of Company Value Of Banking Sub-Sector On The Indonesian Stock Exchange - Luritawati, Aisyah; Takarini, Nurjanti (LP2M IAIN Palopo, 2025)
This study aims to examine the impact of the Capital Adequacy Ratio(CAR), Loan to Deposit Ratio (LDR), and Operational Efficiency Ratio(OER) on firm value in the conventional banking sub-sector listed on theIndonesia Stock Exchange for the 2021–2023 period. This study uses aquantitative approach with purposive sampling techniques and multiplelinear regression analysis methods. Data were obtained from the annualfinancial reports of sampled conventional banking companies over a threeyear period, then analyzed using SPSS version 29. The results show thatCAR contributes to increasing firm value, reflecting the importance ofcapital strength in attracting investor confidence. LDR is also proven tocontribute to firm value, where the level of credit distribution is an importantconsideration for investors in assessing the health and viability of a bank.Meanwhile, OER does not make a significant contribution to firm value,so operational cost efficiency has not been a primary focus for investors inassessing banking performance in the capital market. These findingsindicate that capital strength and the level of credit distribution play animportant role in influencing investor perceptions of firm value, whileoperational efficiency has not been a primary factor in determining firmvalue